IMPROVING THE LABORATORY WORK OF THE PHYSICS COURSE BASED ON THE USE OF ROBOTICS ELEMENTS - Tynysh К.С.; Rystygulova В.Б.; Sydykovа Ж.К.; Zhusipbekova Ш.Е.; Tulenova Г.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article discusses the problem of improving the laboratory work of the physics course using elements of robotics. In the modern education system, the possibilities of robotics are aimed at promoting students’ understanding of physical phenomena, developing their cognitive activity and creative abilities, and improving technical knowledge. In the course of the research, the theoretical and practical aspects of the introduction of robotics elements into the learning process are analyzed. The results of the survey proved that laboratory work based on robotics and the interpretation of physical laws using specific models using robotics contribute to linking students’ theoretical knowledge with practice, forming their research skills and developing skills in the field of STEAM. The integration of robotics into laboratory work in physics and computer science within the STEAM approach enhances the informatization of education, providing interactivity, interdisciplinary and practice-oriented development of digital technologies.